2014
DOI: 10.1111/vop.12159
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy ofCOX‐2 inhibitors in controlling inflammation and capsular opacification after phacoemulsification cataract removal

Abstract: Eyes receiving celecoxib-IOL/PA had better initial control of inflammation. Bromfenac was equally effective compared with PA in controlling inflammation. There was no association between COX-2 inhibitor administration and ocular hypertension. Celecoxib-IOL/PA-treated eyes showed better initial control of PCO (up to 12 weeks), while eyes receiving bromfenac had better long-term control of PCO (56 weeks).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 74 publications
0
13
0
1
Order By: Relevance
“…A standard, commercial NSAID was elected in the oral efficacy study for comparison. Oral carprofen, a selective cyclooxygenase (COX-2) inhibitor, plays an important role in veterinary ocular therapeutics to suppress prostaglandin-mediated anterior uveitis, as seen following intraocular surgery ( 37 , 38 , 40 ). Although COX-2 inhibitors are thought to have wider safety margins compared with COX-1 inhibitors, adverse side effects may still occur including nausea, diarrhea, gastrointestinal ulceration, nephrotoxicosis, platelet dysfunction, and idiosyncratic hepatotoxicosis ( 37 , 38 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A standard, commercial NSAID was elected in the oral efficacy study for comparison. Oral carprofen, a selective cyclooxygenase (COX-2) inhibitor, plays an important role in veterinary ocular therapeutics to suppress prostaglandin-mediated anterior uveitis, as seen following intraocular surgery ( 37 , 38 , 40 ). Although COX-2 inhibitors are thought to have wider safety margins compared with COX-1 inhibitors, adverse side effects may still occur including nausea, diarrhea, gastrointestinal ulceration, nephrotoxicosis, platelet dysfunction, and idiosyncratic hepatotoxicosis ( 37 , 38 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have attempted to determine whether aggressive prevention of postsurgical inflammation can ameliorate PCO; however, the results are equivocal. 27 , 34 , 96 99 However, in each case, only a subset of the proinflammatory pathways active PCS have been targeted, so these studies do not definitively rule out the therapeutic potential of shutting down PCS inflammation in PCO prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Brookshire et al . demonstrated that POH was similar in dogs receiving either bromfenac alone or prednisolone acetate alone as postoperative anti‐inflammatory therapy after cataract surgery . The current study does not ascertain the role of corticosteroids in the generation of POH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports within the veterinary literature have identified IOP elevations following their use in canines presumably as a result of an increase in outflow resistance and from the inhibition of endogenous PG synthesis . A recent canine study showed that there was no association between COX‐2 inhibitor administration and ocular hypertension following cataract surgery …”
Section: Introductionmentioning
confidence: 99%